2009
DOI: 10.1097/mcg.0b013e31818f50b8
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Gastrointestinal Subepithelial Tumors Arising From Muscularis Propria

Abstract: Even small and benign-appearing lesions from muscularis propria may increase in size over time but this increase cannot be considered as an index of malignancy. As most of these lesions are GISTs, a policy of surveillance is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
2
23
0
2
Order By: Relevance
“…They also found that the risk for enlargement was related to initial tumor size [17 mm (P = 0.018) [14]. These observations are confirmed in several other small studies [11,12].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…They also found that the risk for enlargement was related to initial tumor size [17 mm (P = 0.018) [14]. These observations are confirmed in several other small studies [11,12].…”
Section: Discussionsupporting
confidence: 77%
“…More information on the natural history of GISTs can be glistened from natural history studies of small GISTs that are not removed [7,[10][11][12]. Studies by Gill et al and Chien et al and have shown that the majority of subepithileal tumors \3 cm including GISTs do not change in size with a mean follow-up of 20.7 and 23 months, respectively [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…The management of GISTs that measure <2 cm in greatest dimension is more questionable. [57][58][59] Although the low risk of progression of GISTs that measure <2 cm offers the possibility of a more conservative approach, a reliable mitotic index cannot be determined by biopsy or fine-needle aspiration, thus preventing the identification of those at higher risk. Therefore, both observation and resection can well be considered for GISTs that measure from 1 cm to 2 cm in greatest dimension, and the risks and benefits of one versus the other should be discussed with the patient.…”
Section: Gastrointestinal Stromal Tumorsmentioning
confidence: 99%
“…A significant increase in the size of an SET was defined as an increase of the longest diameter by more than 25% in the last EUS feature compared with the initial EUS examination. 15,16 All of the photographs of the enrolled SETs were reviewed by one skilled endoscopist.…”
Section: Eusmentioning
confidence: 99%
“…Unfortunately, there have been only a few studies analyzing the natural history of SETs using EUS examination. [19][20][21][22] In the current study, 11.4% of SETs less than 30 mm increased significantly in size during a mean period of 22.8 months. The proportion of significant growth was 9.5% and 12.5% in the esophagus and stomach, respectively.…”
mentioning
confidence: 99%